Design of an Adaptive Tutoring System Based on Retrieval-Enhanced Generation and Dynamic Profiling: Promoting Educational Equity - Ju, Yongzhen (International Journal of Computer Science and Information Technology, 2026)
Against the backdrop of Education Informatization 2.0 and the scarcity of high-quality educational resources in rural areas due to urban-rural disparities in China, this study addresses the challenges faced by education products based on general-purpose large models. These challenges include the unavoidable occurrence of "knowledge hallucinations" and difficulties in accurately matching teaching content. this paper employs RAG algorithms and dynamic student profiling to establish a personalized learning assistance platform. Integrating methods such as OCR and FAISS, it constructs real-time profiles and utilizes a dual-model collaborative operation mode for Q&A. A precise resource recommendation scheme ensures the accuracy of provided learning materials, genuinely aligning with students' individual circumstances to fulfill their personalized educational needs.